2018
DOI: 10.1037/edu0000220
|View full text |Cite
|
Sign up to set email alerts
|

Signaling text–picture relations in multimedia learning: The influence of prior knowledge.

Abstract: Multimedia integration signals highlight correspondences between text and pictures with the aim of supporting learning from multimedia. A recent meta-analysis revealed that only learners with low domain-specific prior knowledge benefit from multimedia integration signals. To more thoroughly investigate the influence of prior knowledge on the multimedia signaling effect in a more ecologically valid context, we conducted a quasi-experimental field study with 8th graders. They learned with a digital multimedia te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 56 publications
2
37
0
4
Order By: Relevance
“…Ozcelik et al (2009) and Scheiter and Eitel (2015) used spatialcolor schemes reducing the distance between the text and the picture or highlighting the corresponding verbal and non-verbal elements in one color. However, such tools were shown to be effective only for poorly prepared students, but do not influence the results of students with a higher level of training (Kalyuga et al, 2003;Sweller et al, 2003;Kalyuga, 2007;Richter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ozcelik et al (2009) and Scheiter and Eitel (2015) used spatialcolor schemes reducing the distance between the text and the picture or highlighting the corresponding verbal and non-verbal elements in one color. However, such tools were shown to be effective only for poorly prepared students, but do not influence the results of students with a higher level of training (Kalyuga et al, 2003;Sweller et al, 2003;Kalyuga, 2007;Richter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, similar to the results of the text research, multimedia learning research pointed out an expertise reversal effect (Sweller et al, 2003;Kalyuga, 2014), which states that learners with low prior knowledge are more likely to benefit from the text's adjunct visual representation than learners with high prior knowledge are. Notably, this expertise reversal effect was found in studies on signaling (Spanjers et al, 2011;Richter et al, 2017;Richter and Scheiter, 2019). Moreover, the cognitive-affective theory of multimedia learning (Moreno, 2005(Moreno, , 2006 addressed the question of a link between affect and comprehension.…”
Section: Learning From Text and Picturementioning
confidence: 76%
“…Indeed, the guidance from CRS probably does not improve the generation of inferences beyond the benefits of high text cohesion. Previous research has showed that the generation of inferences is supported by both verbal references in the text and signaled visual references in the picture, both of which were found to support comprehension individually (e.g., McNamara, 2001 ; Richter et al, 2017 ). Therefore, we expected the interaction to be observed only when the generation of inferences was required and not for text-based questions.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations